CONCEPTUAL AND METHODOLOGICAL FRAMEWORK FOR THE COMPREHENSIVE PROTECTION OF SUBJECTS AND OBJECTS OF INFORMATION RELATIONS - I. S. Klimenko; N. A. Medetov (Современная наука и инновации)
Actualisation of the problem of complex protection of information objects is the result of the rapid development of information technologies, which not only led to the modernization of information relations, but also revealed the necessity to create complex information security systems as a significant component of the information security concept of the particular region and the whole state. Information security, in fact, is the protection of subjects and objects of information relations from internal and external threats. The problems of organizing complex protection of subjects I objects of information relations should be studied because of an intensity of information flows, increasing requirements for the level of protection for confidential information, the growing number of attacks on data storage systems and communication links, etc.